How shifting occupational composition has affected the real average wage. - Keller, Rebecca (Monthly Labor Review, 2009)
OES data from 2002 — 2007 reveal that an overall shift in employment towards occupations with lower mean wages hindered growth in the U.S. real average wage and that wage growth was concentrated in higher paying occupations; the data also show a shift in employment from the middle-paying occupations to the highest and lowest paying occupations